2021
DOI: 10.31018/jans.v13i4.2936
|View full text |Cite
|
Sign up to set email alerts
|

Phytostimulation and growth promotion activities of Trichoderma spp. on groundnut (Arachis hypogaea L.) crop

Abstract: Groundnut (Arachis hypogaea L.) suffers from many soil borne pathogens that deteriorate the quality of the seeds and are responsible for high yield loss. Practically Trichoderma sp. is used for seed treatment, it minimizes the seed and soil borne pathogens and supports plant growth promotion activities. In the present study, five different isolates of Trichoderma spp. were isolated from groundnut (A. hypogaea ) rhizosphere soil. All the five isolates were confirmed by morphological methods and using molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…For the peanut (Arachis hypogaea) crop, Ayyandurai et al (2021) [96] obtained five species of Trichoderma in India. This makes this crop more diverse than the Mexican crops analyzed in this work, with the presence of one species, T. harziaum [10].…”
Section: Discussionmentioning
confidence: 99%
“…For the peanut (Arachis hypogaea) crop, Ayyandurai et al (2021) [96] obtained five species of Trichoderma in India. This makes this crop more diverse than the Mexican crops analyzed in this work, with the presence of one species, T. harziaum [10].…”
Section: Discussionmentioning
confidence: 99%
“…La estimulación de crecimiento y los incrementos en productividad de cultivos asociados a inoculaciones con Trichoderma se han observado en un amplio número de especies de plantas como clavel, rábanos, tomate, lechuga, maíz, maní y frijol, entre otros (Gravel et al 2007, Hoyos 2011, Gupta et al 2014, Ayyandurai et al 2021. Se ha encontrado que aislamientos de Trichoderma contribuyen al crecimiento longitudinal de las raíces de maíz y algunos pastos, que hacen que estos cultivos sean más resistentes a la sequía y enfermedades, además, se ha observado que, en el caso del maíz, requiere un 40% menos de fertilizantes nitrogenados en relación con las plantas que no están inoculadas Agronomía Costarricense 46(2): 47-60.…”
Section: Discussionunclassified
“…se utilizan para el tratamiento de semillas y suprimen significativamente el crecimiento de microorganismos patógenos de las plantas, que mejora de está manera, la tasa de crecimiento de las plantas (Sidiquee et al 2017). El efecto podría ser particularmente fuerte en términos de promoción del crecimiento de raíces y de los tallos mediante el aumento en longitud, grosor, área foliar, contenido de clorofila, y rendimiento (tamaño o número de flores o frutas) (Ayyandurai et al 2021). Estudios realizados con diferentes especies con Trichoderma tanto a nivel de invernadero como de campo, en diferentes cultivos como pepino, frijol, berenjena, lechuga, pimiento y tomate (Gupta et al 2014, Sani et al 2020, maní (Ayyandurai et al 2021) y el roble plateado (Umaschankar et al 2012), entre otros.…”
Section: Introductionunclassified
“…cepae of 1.29 cm @ 15% concentration, followed by groundnut cake at 1.36 cm @ 30% concentration, 2.28 cm was recorded as the least inhibition zone in this Pungam cake at 15% concentration. Similarly, Ayyandurai et al (2021) tested the different oilcake extracts against the Sclerotium rolfsii by poisoned food technique. Among them, mahua cake (10%) recorded the maximum inhibition zone of 1.29cm, followed by neem cake (10%), which recorded a 1.93cm inhibition zone.…”
Section: Efficacy Of B Subtilis Isolates Against F Oxysporum Fsp Cepaementioning
confidence: 99%
“…But interestingly majority of Trichoderma species are plant growthpromoting fungi that generate phytohormones and the 1 -aminocyclopropane-1-carboxylate (ACC) deaminase enzyme as well as Trichoderma appears to be the best candidate among nonpathogenic fungal microorganisms for use in green technologies due to its broad bio-fertilization and bio-stimulatory potential (Tyskiewicz et al, 2022). Ayyandurai et al (2021) found that Trichoderma longibrachiatum induce growth promotion activities in groundnut plants and successfully inhibits the growth of soil-borne pathogens. Deshmukh et al (2016) reported that soil amendments containing various organic matter types are crucial for disease control and soil quality improvement.…”
Section: Introductionmentioning
confidence: 99%